Creative approaches in music teaching: Possibilities of Web 2.0 technologies. (June 2021) - Lv, Hua Zhen; Luo, Junyi
Highlights: The study aims to reveal the potential of the use of online learning resources. The research is based on the direct experimental research in the music classroom. The study relies on quantitative and qualitative methods of data collection. Abstract: The study aims to experimentally reveal the potential of the use of online learning resources, namely SmartMusic, eMusicTheory, and Dolmetsch Music Theory, to improve qualitative music learning indicators in such skills as sight-singing, ear training, rhythmic reading, musical notation and performing skills. Much of the research is based on the direct experimental research in the music classroom. Google Forms were used to create an online questionnaire containing questions to be rated based on the Likert scale. The evaluators were music teachers from Lishui University (China). The research sample involves a group of students enrolled in the 2018/2019 and 2019/2020 choir singing classes. The sample consists of 56 students (64 % men and 36 % women). The participants were randomly divided into experimental and control groups. A survey of students suggests that the use of SmartMusic, eMusicTheory, and Dolmetsch Music Theory is perceived positively. Pre- and post-assessments showed that when using SmartMusic to train sight-singing, the gap between the mean improvement score of the experimental and control groups was 14 points. The use of eMusicTheory and Dolmetsch Music Theory for ear training led to the gap of 6.7 points, and the use of SmartMusic, eMusicTheory, and Dolmetsch Music Theory to train rhythmic reading, performance and musical notation skills resulted in the gap of 6.2 points, 3.3 points, and 2.4 points, respectively. The study can be of interest to music educators, education administrators, and researchers who are seeking to improve the quality of music teaching and learning by leveraging the power of Internet platforms.